PERAN DALIHAN NA TOLU DALAM PELAKSANAAN UPACARA PERKAWINAN MASYARAKAT BATAK TOBA DI KELURAHAN TANJUNG PENYEMBAL KOTA DUMAI - Nainggolan, Riris; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The marriage law of the Toba Batak indigenous people regulates the role of Dalihan Na Tolu. The role of Dalihan Na Tolu is something that cannot be separated from the culture of society in the Toba Batak tradition. In a legitimade marriage, Dalihan Na Tolu has outlined and stipuled rules and regulations regarding various social relations, bothÂ between husband and wife, between parents and siblings from each of them either party. The problems that will be discussed in this paper are about the social actors included in the Dalihan Na Tolu Toba Batak kinship system and the role of Dalihan Na Tolu in the marriage ceremony of the Toba Batak people. The approach method used in this research in descriptive qualitative research method. The data used are primary data and secondary data, and data collection is done by conducting interviews, observation and documentation. The results showed that the life of the Toba Batak indigenous people were very concerned with the collaboration between the roles of the Dalihan Na Tolu elements themselves, namely Hula-hula, Dongan Tubu, and Boru. This is also inseparable from the proverbial meaning of Dalihan Na ToluÂ which unites Somba Marhula-hula, Manat Mardongan Tubu, and Elek Marboru because they contain a deep meaning and muthlak must be done if they want to prosper their lives. As fot the duty and role of Dalihan Na Tolu it began to appear at the stages of the Marhata Sinamot, Martuppol, Manjalo Pasu-Pasu Parbogason and Pesta Unjuk. In addition, the results of the study also showed that both Hula-hula. Dongan Tubu, and Boru worked together in carrying out their duties and roles.Keywords :Dalihan Na Tolu, Batak Marriage